Onboarding : how to get your new employees up to speed in half the time - Bradt, George B.; Vonnegut, Mary. (Hoboken, N.J. : Wiley, 2009)
This is a guide to getting new employees recruited, oriented, and productive - Fast. 'Onboarding', a growing trend in the business community, is a focused methodology that gets people in new roles up to speed quickly and efficiently. This book guides you through a process that enables you to recruit, orient, and enable your new employees to get the job done. Learn how to inspire and encourage your new employees to deliver better results faster. George Bradt and Mary Vonnegut's "Onboarding" helps ensure that your new employees are productive and efficient from day one. You'll learn how to help them assimilate into your corporate culture and accelerate their learning. Onboarding is one of the hottest trends in business. This is the first book about onboarding. George Bradt is a leading speaker and consultant, and the author of "The New Leader's 100-Day Action Plan". For business leaders and managers who want well-trained, responsive, efficient, and effective employees, "Onboarding" helps you get the best from your new employees
Front Matter -- Prepare for Your New Employee's Success Before You Start Recruiting. Understand the Organization-Wide Benefits of a Total Onboarding Program: An Executive Summary -- Clarify Your Destination and Messages to the Candidate and the Organization -- Craft Your Time Line, Write a Recruiting Brief, and Align Your Stakeholders -- Recruit in A Way That Reinforces Your Messages. Create a Powerful Slate of Potential Candidates -- Evaluate Candidates Against the Recruiting Brief While Pre-Selling and Pre-Boarding -- Make the Right Offer, and Close the Right Sale the Right Way -- Give Your New Employee A Big Head Start Before Day One. Co-Create a Personal Onboarding Plan with Your New Employee -- Manage the Announcement to Set Your New Employee Up for Success -- Do What It Takes to Make Your New Employee Ready, Eager, and Able to Do Real Work on Day One -- Enable and Inspire Your New Employee to Deliver Better Results Faster. Make Positive First Impressions Both Ways -- Speed Development of Important Working Relationships -- Provide Resources, Support, and Follow-Through -- Appendices. Appendix I: Organization-Wide Transformation -- Appendix II: Sourcing Candidates on the Web -- Notes -- Glossary -- References -- About the Guest Experts -- About the Authors -- Index.
Includes bibliographical references and index.
Print version record.
English.
John Wiley and Sons
Keywords: Employees -- Recruiting; Employee orientation; Employee motivation; Personnel -- Recrutement; Personnel -- Introduction au travail; Personnel -- Motivation; BUSINESS & ECONOMICS -- Human Resources & Personnel Management; BUSINESS & ECONOMICS -- Workplace Culture; Employee motivation; Employee orientation; Employees -- Recruiting; Arbeitsmotivation; Neuer Mitarbeiter; Personalbeschaffung; Unternehmen